PENERAPAN MEDIA PEMBELAJARAN AUDIO VISUAL DALAM PEMBELAJARAN MUSIK TRADISIONAL UNTUK MENINGKATKAN MINAT BELAJAR SISWA MI - Rofita Aprilia Putri Mardiana Al Sidiq; BZ, Zakiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The objective of this study is to determine how the implementation of audio-visual media influences students’ interest and participation in cultural arts learning, particularly traditional music material in Grade IV at MIN 1 Probolinggo. A descriptive qualitative method was employed, with data collected through observation, interviews, and documentation. All fourth-grade students participating in cultural arts lessons were involved as the research subjects. The use of audio-visual media in the form of animations integrating sound and visual elements was proven to significantly enhance students’ learning interest, making them more enthusiastic, focused, and active, including in asking questions, engaging in discussions, and understanding traditional music material. The increase in students’ learning interest can also be illustrated through a developmental graph showing an upward trend from one meeting to the next. In addition, audio-visual media assists students in grasping traditional music concepts more concretely, including recognizing musical instruments, sounds, and regional songs. The findings conclude that audio-visual media plays an effective role in improving students’ interest, participation, and understanding in cultural arts learning. To support optimal implementation, it is recommended that supporting facilities be provided and that teachers’ competencies be enhanced through regular training. Future studies are expected to further explore the use of audio-visual media by considering the conditions of school facilities and infrastructure.